INPUT AND OUTPUT LEVELS OF IRRIGATION PROGRAMMES FOR VEGETABLE PRODUCERS MANAGED BY THE GOVERNMENT AND FARMERS IN NORTH WEST NIGERIA - Abubakar, A. D.; Ahmed, B.; Sanni, S. A.; Oladimeji, Y. U.; Akpoko, G. J. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
This study examined the level of vegetable production and estimate their production efficiency in North West Nigeria. In order to achieve this, a sample size of 360 vegetable farmers from Jigawa (110), Kano (137) and Katsina (113) States were randomly selected using a multi-stage sampling technique. The data were collected using structured questionnaires and interview scheduled. The tools of analysis include descriptive statistics and Cobb-Douglas stochastic frontier production model. The results of the production efficiency analysis showed that seed and labour significantly influenced the level of production of tomato, pepper and onion at 1% level of probability. There was also a strong correlation between the level of production and the type of irrigation scheme thereby confirming the variability in the level of vegetable production across government managed irrigation scheme (GMIS) and farmers managed irrigation scheme (FMIS). The significant deviation from the expected maximum level of production efficiency was impacted by the presence of technical inefficiency which in turn was determined by a number of factors On average, farmers under GMIS and FMIS were 64% and 67% technically efficient in tomato production, 81% and 69% technically efficient in pepper farming and 69% and 78% technically efficient in onion cultivation, respectively. The most important determinants of allocative inefficiency in vegetable production were the age of the household head, farming experience, type of irrigation scheme and the soil properties. On average, vegetable farmers under GMIS and FMIS were 85% and 65% allocative efficient in tomato production, 76% and 74% allocative efficient in pepper farming and 77% and 81% allocative efficient in onion cultivation, respectively. Consequently, it was derived that, on average, vegetable farmers under GMIS and FMIS were 55% and 50% economically efficient in tomato production, 64% and 50% economically efficient in pepper farming and 53% and 64% economically efficient in onion production, respectively. It was concluded that vegetable farming system under GMIS is more efficient and sustainable than FMIS, judging from efficiencies parameters. Inputs such as labour, seed and fertilizer were inelastic with respect to output, hence, farmers are encouraged to be train by extension agents in order to determine the most appropriate rate of inputs to use.